A novel dry-blending method to reduce the coefficient of thermal expansion of polymer templates for OTFT electrodes - Ye, Xiangdong; Tian, Bo; Guo, Yuxuan; Fan, Fan; Cai, Anjiang (Beilstein Journal of Nanotechnology, 2020)
Among the patterning technologies for organic thin-film transistors (OTFTs), the fabrication of OTFT electrodes using polymer templates has attracted much attention. However, deviations in the electrode alignment occur because the coefficient of thermal expansion (CTE) of the polymer template is much higher than the CTE of the dielectric layer. Here, a novel dry-blending method is described in which SiO2 nanoparticles are filled into a grooved silicon template, followed by permeation of polydimethylsiloxane (PDMS) into the SiO2 nanoparticle gaps. The SiO2 nanoparticles in the groove are extracted by curing and peeling off PDMS to prepare a PDMS/SiO2 composite template with a nanoparticle content of 83.8 wt %. The composite template has a CTE of 96 ppm/°C, which is a reduction by 69.23% compared with the original PDMS template. Finally, we achieved the alignment of OTFT electrodes using the composite template.
Keywords: coefficient of thermal expansion; dry blending; organic thin-film transistors (OTFTs); OTFT electrodes; PDMS/SiO2 composite template